STUDY UPON THE CAVITATION PHENOMENON OF THE ROTORS - Beazit ALI; Gheorghe SAMOILESCU (Fiabilitate şi Durabilitate)
The main problem of the hydrodynamics of cavitation implosion of a single bubble, consists inpressure and velocity fields determination, including the collapse velocity of the bubble wall. By analysis thetheoretic and experimental phenomenon it establish the implicit function which describes this phenomenon. Byapplication the  theorem for this implicit function it finds the criterion equation of phenomenon.Depending on operating condition various cavitation patterns can be observed on a body surface astravelling bubbles, attached sheet cavitation, shear cavitation or vortex cavitation. Leading edge attachedpartialcavitation is commonly encountered on rotor blades or on hydrofoil. It corresponds to the case for whichavapor cavity is attached in the vecinity of the leading edge and extends over a fraction of the foil surface. Itgenerally takes places at incidence angles for which a leading edge pressure peak occurs and reduced belowtheliquid vapor pressure. At the early phases of development, leading edge partial cavitation is steady.